Concepts and Patterns of Destination Leadership and Their Application in Sports Tourism: A Scoping Review - Mansoor Hassoon, Hayder; Yousefi, Bahram; Hasani, Zohreh; Moradi, Erfan; Norouzi Seyed Hosseini, Rasool (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to conduct a scoping review of research related to the concepts, models, and capabilities of leadership in tourism destinations, particularly in the context of sports tourism, and to address questions that can contribute to leadership development in these destinations. Methodology: The research method was designed based on the five-step framework by Arksey and O’Malley (2005), with data extracted from three credible databases, including Web of Science, Scopus, and Google Scholar, and reviewed following PRISMA guidelines. After eliminating duplicates and applying inclusion and exclusion criteria, 48 articles were selected for final analysis. Findings: Results indicate that researchers are increasingly focused on a novel paradigm emphasizing network leadership over individualistic and hierarchical models. However, no unified or shared definition of leadership in tourism destinations has emerged. Leadership models proposed for success in tourism destinations include systemic, distributed, collective, and shared leadership. Additionally, essential capabilities for destination leadership include networking, analytical skills, influence, economic acumen, vision development, strategic planning, and generating enthusiasm. Finally, the relationship between sports and tourism destinations can be analyzed through three dimensions: "destination as a product" (active sports tourism), "venue for product delivery" (sporting events), and "part of the product package" (sports as a destination attraction). Conclusion: Within the framework of the network relationship paradigm, three leadership models—inter-organizational, inter-sectoral, and intra-sectoral—can be proposed.